Substandard medicines: a greater problem than counterfeit medicines? - Sammons, Helen M.; Choonara, Imti (BMJ Publishing Group, 2017)
Substandard medicines are medicines which have failed to pass the quality measurements and standards set for them.1 They should be distinguished from counterfeit (falsified) medicines which are deliberately and fraudulently mislabelled. Combining the two together however is not helpful. They are different problems that require different solutions. Substandard and counterfeit medicines are a widespread problem in low-income and lower–middle-income countries. A systematic review showed that the median prevalence of substandard and counterfeit medicines was 28.5%.1 This ranged from 11% to 48% in individual studies. The 15 studies were all limited to antimicrobial drugs, with the majority (13) including antimalarials. Only 2 of the 15 studies within the systematic review differentiated between substandard and counterfeit medicines. Both studies involved antimalarial drugs in South East Asia. They both found that counterfeit medicines were a greater problem than substandard medicines. The biggest problem in relation to the quality of the medicines tested was an inadequate amount of the active ingredient.